An analysis of small-signal gate-drain resistance effect on RF power MOSFETs. - Yo-Sheng Lin (IEEE Transactions on electron devices)
The anomalous dip in scattering parameter S11 of RF power MOSFETs with drain-to-spacer offset is explained quantitatively for the first time. Our results show that, for RF power MOSFETs, the input impedance can be represented by a simple series RC circuit at low frequencies and a "shifted" parallel RC circuit at high frequencies. The appearance of the anomalous dip of S11 in a Smith chart is caused by this inherent ambivalent characteristic of the input impedance. It is found that an increase of drain-to-spacer offset enhances the anomalous dip. In addition, the anomalous dip in S11 of RF power n-MOSFETs can also be interpreted in terms of poles and zeros.